Preparation and structural characterization of hybrid composites of semiconductor oxides with amorphous carbon - Zocolaro, Gabriela D. C. [UNESP]; Silveira, Gisele S. [UNESP]; Nobre, Marcos A. L. [UNESP]; Lanfredi, Silvania [UNESP] (Trans Tech Publications, 2018)
Organic/inorganic hybrids composites type have been reported as an alternative for the preparation of multifunctional materials with superior properties to those of individual constituents. In this work, hybrid composites of semiconductor oxides with amorphous carbon (C/ZnO and C/TiO2) were synthesized by partial pyrolysis method and characterized by X-ray diffraction (XRD), infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The XRD patterns showed the presence of crystalline diffraction lines overlaid by diffraction halos. Infrared spectra showed bands associated to the stretching of Zn-O and Ti-O bonds, as well as bands assigned to the stretching vibrations of C-O, C=O and C-H. Micrographs showed the formation of organized structures in the shape of plates and agglomerates of particles. Structural characterizations showed that the composites present the characteristics of the pristine semiconductors as well of the amorphous carbon matrix, showing a great synergism between C/semiconductor.
Keywords: Amorphous carbon; Hybrid composites; Semiconductor